The Influence of Principal's Role and Organizational Commitment on Teachers’ Work Motivation in Public Elementary Schools - Suwarsi, Suwarsi; Soedjono, Soedjono; Nugroho, Aryo Andri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to examine the influence of the principal’s role and organizational commitment on teachers’ work motivation in public elementary schools in Boja District, Kendal Regency. Employing a quantitative approach with an ex post facto survey design, data were collected from 103 teachers selected through stratified random sampling from a total population of 138 teachers across 16 public elementary schools. The primary data source comprised teacher responses to validated Likert-scale questionnaires measuring three variables: the principal’s role, organizational commitment, and teacher work motivation. Data analysis, conducted using SPSS 26, included Pearson product-moment correlation to assess the strength of bivariate relationships, simple linear regression to evaluate the individual influence of each independent variable, and multiple linear regression to examine their combined effect. Hypothesis testing was performed at a significance level of α = 0.05 to determine the statistical validity of each relationship. The results indicated that the principal’s role had a significant positive influence on teacher motivation, accounting for 22.7% of the variance, while organizational commitment had a slightly greater influence, contributing 24.4%. When analyzed simultaneously, both variables explained 32.8% of the variance in teacher motivation, demonstrating a moderately strong and statistically significant combined effect. These findings underscore the importance of enhancing school leadership and cultivating organizational commitment as strategic efforts to improve teacher motivation—an essential factor in sustaining teacher performance and advancing educational outcomes.